การจัดอัตรากำลังบุคลากรทางการพยาบาลในห้องคลอดตามปริมาณภาระงาน : กรณีศึกษาโรงพยาบาลรามาธิบดี - นิตยา โรจนนิรันดร์กิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To study nursing hours per day of delivery patients classified by patient classification and to determine the number of nursing personnel according to workload in delivery room, Ramathibodi Hospital. Completed each nursing activities and indirect nursing activities for delivery patient by nursing personnel which composed of 22 professional nurses and 23 nonlicensed practical nurses were observed by the observer (researcher and 6 researcher assistants). The observer recorded the start and stop time of each nursing activity. In addition unit activities and personal activities were used self-reporting by nursing personnel. The research instruments consisted of patient classification form, direct and indirect nursing activity form. Data were calculated by using Brown s formula. The research findings were as follows 1. The average of nursing hours per day of delivery patients in each of 5 categories from 1- 5 were 6.24, 7.16, 7.75, 9.92 and 10.90 respectively. The average of nursing hours per day of newborns were 1.61. 2. The number of nursing personnel according to workload in delivery room, Ramathibodi Hospital were 26 professional nurses and 20 nonlicensed practical nurses. 3. The ratio of professional nurses : nonlicensed practical nurses in day shift, evening shift and night shift = 7:6, 6:4 and 4:4 respectively.